The Effect of Home Visit on Islamic Education Learning Outcomes of SMKN 2 Students in Pagar Alam City - Sari, Novita; Sari, Wulan; Manto, Manto (Innovative: Journal Of Social Science Research, 2024)
Exams and assignments help students acquire learning goals, which they then demonstrate by actively asking and answering questions that build on these objectives. Many people in the academic community believe that students' final grades do not really reflect their academic achievement. The learning outcomes of a student may still be recognized as a measure of achievement in the cognitive sphere. This research aimed to examine the relationship between student home visits, PAI learning results, and the impact of home visits on Islamic education learning outcomes among students at State Vocational High School 2 in Pagar Alam City. An example of a descriptive quantitative study that did not succeed is this one. It uses interviews and questionnaires to characterize different parts of the population from a sample. Students at SMKN 2 Kota Pagar Alam's class X Marketing I benefit academically from home visit services. Student achievement in the classroom is directly proportional to the quality of home visit programs. Consistent with previous research by Halam, this study found that home visit services are effective when families and professional teachers work together to boost students' motivation to learn and sustain that motivation over time, leading to improved learning outcomes.